"What? So What? Now What?" Applying Borton and Rolfe's Models of Reflexive Practice in Healthcare Contexts. (29th May 2016) - Skinner, Martyn; Mitchell, David
Abstract : Healthcare chaplains as healthcare professionals are expected to use reflective practice to develop their work. This article describes how reflexive practice is critical to practitioners doing this. It outlines how Terry Borton's process of reflection arose out of a secondary school context; and contends that his simple three step model is capable of facilitating profound insights in healthcare too. The way in which Gary Rolfe expands Borton's model is explained, showing how he was seeking to make it more comprehensive and credible. Finally, a way of combining Borton and Rolfe's models is described and pictured. It is argued that it is both structured and flexible enough to fit the experiences, learning needs and time available to healthcare practitioners.